2016
DOI: 10.1120/jacmp.v17i2.5747
|View full text |Cite
|
Sign up to set email alerts
|

Application of dose kernel calculation using a simplified Monte Carlo method to treatment plan for scanned proton beams

Abstract: Full Monte Carlo (FMC) calculation of dose distribution has been recognized to have superior accuracy, compared with the pencil beam algorithm (PBA). However, since the FMC methods require long calculation time, it is difficult to apply them to routine treatment planning at present. In order to improve the situation, a simplified Monte Carlo (SMC) method has been introduced to the dose kernel calculation applicable to dose optimization procedure for the proton pencil beam scanning. We have evaluated accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…On the other hand, Kohno et al reported that the conventional pencil beam algorithm (PBA) dose calculation overestimated 400 -500 cGy (RBE) for minimum physical dose to the CTV relative to the physical dose calculated by the FDC [19]. Mizutani et al also reported that the D95 for PTV obtained by the simplified Monte Carlo method [32] [33] was ~25% smaller than that obtained by conventional pencil beam algorithm (PBA) dose calculation [34]. Thus, for the target volume, these results indicate that the dose errors by the physical dose calculation model would be greater in current proton beam therapy than those calculated by the RBE calculation model.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kohno et al reported that the conventional pencil beam algorithm (PBA) dose calculation overestimated 400 -500 cGy (RBE) for minimum physical dose to the CTV relative to the physical dose calculated by the FDC [19]. Mizutani et al also reported that the D95 for PTV obtained by the simplified Monte Carlo method [32] [33] was ~25% smaller than that obtained by conventional pencil beam algorithm (PBA) dose calculation [34]. Thus, for the target volume, these results indicate that the dose errors by the physical dose calculation model would be greater in current proton beam therapy than those calculated by the RBE calculation model.…”
Section: Discussionmentioning
confidence: 99%
“…This means that dose error depends on a location of a target, the presence of a heterogeneity and beam direction. Dose differences between the TPS and actual irradiation in these plans are expected [19].…”
Section: Introductionmentioning
confidence: 99%